2010
DOI: 10.1111/j.1369-1600.2010.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Severity of dependence modulates smokers' neuronal cue reactivity and cigarette craving elicited by tobacco advertisement

Abstract: Smoking-related cues elicit craving and mesocorticolimbic brain activation in smokers. Severity of nicotine dependence seems to moderate cue reactivity, but the direction and mechanisms of its influence remains unclear. Although tobacco control policies demand a ban on tobacco advertising, cue reactivity studies in smokers so far have not employed tobacco advertisement as experimental stimuli. We investigated whether tobacco advertisement elicits cue reactivity at a behavioral (subjective craving) and a neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 39 publications
3
57
2
2
Order By: Relevance
“…Consistent evidence has shown that salient cues are able to trigger a vast and personalized array of physiological, psychological, and behavioral responses similar to those experienced during substance use (Beaver et al, 2011;Hogarth, Dickinson, & Duka, 2010;Vollstädt-Klein et al, 2011). Drug CR is one of the major factors involved in the relapse into drug-seeking and drug-taking behavior, and therefore it is an important issue for the development of innovative clinical and rehabilitative approaches.…”
Section: Motor Cognition In Asd: Motor Anomalies Impacting On Social mentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent evidence has shown that salient cues are able to trigger a vast and personalized array of physiological, psychological, and behavioral responses similar to those experienced during substance use (Beaver et al, 2011;Hogarth, Dickinson, & Duka, 2010;Vollstädt-Klein et al, 2011). Drug CR is one of the major factors involved in the relapse into drug-seeking and drug-taking behavior, and therefore it is an important issue for the development of innovative clinical and rehabilitative approaches.…”
Section: Motor Cognition In Asd: Motor Anomalies Impacting On Social mentioning
confidence: 99%
“…This view hypothesizes that the progression from use to abuse and then dependence may be characterized as the transition from voluntary to habitual and progressively compulsive drug use. From a neurobiological perspective, such a transition would reflect a dynamic shift in the neural loci of control over behavior (i.e., from the ventral to dorsal striatum, in combination with a progressive decrease in prefrontal cortical control; Everitt & Robbins, 2013;Garavan et al, 2000;Volkow et al, 2006;Vollstädt-Klein et al, 2011). Although the role of motor processes in the neurobiology of addiction has been widely underestimated or even neglected in past decades (Yalachkov, Kaiser, & Naumer, 2010), more recently it has been hypothesized that motor mechanisms play Fig.…”
Section: Motor Cognition In Asd: Motor Anomalies Impacting On Social mentioning
confidence: 99%
“…Both nicotine and conditioned cues have been shown to maintain cigarette smoking and trigger relapse (Heishman et al, 2010;Henningfield and Goldberg, 1983;Janes et al, 2010a;Rose, 2006;Vollstadt-Klein et al, 2010). While the majority of cigarette smokers endorse the desire to quit, reported abstinence rates after 12 months are in the modest region of 5-17% (Hughes et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…11 Although craving may be induced by individual cues, the reality is that craving generally arises because of a complex association of emotional, environmental, autobiographical, and sensory information. To generate a more realistic craving state, recent studies have begun to use dynamic and complex virtual environments, 1,[12][13][14] which allow users to navigate through the environment and become fully immersed in it.…”
mentioning
confidence: 99%